Phase transitions and magnetoelectricity in Fe implanted TlInS2 and TlGaSe2 ferroelectric crystals - Mikailzade, F.; Maksutoglu, M.; Khaibullin, R. I.; Mammadov, T. G. (Taylor & Francis Ltd, 2023)
The dielectric constant measurements of Fe implanted TlInS2 and TlGaSe2 crystals without and under application of constant magnetic field have been performed. It has been observed that the implantation of the crystals with Fe ions caused the formation of ferromagnetic layer in the irradiated region, which leads to considerable shifts of the successive incommensurate and commensurate phase transitions to high temperatures in the heating regime. Remarkable shifts of the phase transition temperatures back to the low temperature region on heating of the samples were observed on applying the magnetic field perpendicularly to the implanted surface. None changes of the phase transition temperature points on measurements of the samples have been observed in cooling regime. The obtained results are interpreted as magnetodielectric effects that resulted from magnetoelectric coupling between ferromagnetic and ferroelectric constituents of the composite structure.
Keywords: Nanostructures; phase transitions; dielectric properties; multiferroics